Habitat analysis of Formica rufa AND Formica polyctena (HYMENOPTERA; FORMICIDAE) preferences in KYIV CITY, Ukraine according to Vegetation - Stukalyuk, Stanislav; Kozyr, Mykola; Goncharenko, Igor (Penerbit Universiti Kebangsaan Malaysia, 2024)
The habitats of two species of Red Wood Ants (RWA, Formica rufa Linnaeus, 1761, Formica polyctena Foerster, 1850) were assessed in urbanized forests in Kyiv city (Ukraine). Descriptions of vegetation in the study sites of RWA were used for phytoindicative assessment of environmental conditions according to eight factors. The aim of this study is to analyze the ecological requirements of two species RWA in the urbanized forests of Kyiv using the phytoindication approach. The study was conducted in 2020-2022 on the territory of two forest areas in Kyiv, represented by deciduous (Golosiivsky forest) and mixed forests (Svyatoshinsky forest). Seven RWA nest complexes were found and mapped, three nest represent Formica rufa (152 anthills) and four nest complexes represent F. polyctena (132 anthills). It has been established that anthills are located near trees, usually conifers. In mixed forests, anthills are larger in both species. The height and diameter of the anthill are directly proportional to the number of forage trees visited. Ecological analysis of habitats of RWA using a phytoindication approach revealed the following factors significant for RWA: a) natural habitats (F=95.066, P-value = 1.9e-11), F. polyctena is more sensitive to the anthropogenic factor; b) humidity of habitats (p-value = 2e-09). The ecological humidity amplitude is wider in F. rufa (sd = 0.98 in F. polyctena vs sd = 3.85 in F. rufa); c) thermal regime (P-value = 7.7e-04), F. polyctena has a higher value (mean = 57.02). The amplitude value for the thermal regime is wider in F. rufa (sd = 2.36 in F. polyctena vs sd = 6.85 in F. rufa), i.e., F. rufa is a more eurytopic (plastic) species. There is no separation of the habitats of the two species of RWA, and, despite the difference in optima, the ecological amplitudes of F. polyctena and F. rufa largely overlap.